The effects of parental influence on their children’s career choices - Clutter, Chance (Kansas State University, 2010)
An exploration of parents’ critical role in their children’s career choices and aspirations was the primary focus of this paper. This includes a brief history of past career counseling techniques, which began in its formative years by assessing the client’s personality to determine proper occupational fit. It has now progressed to the postmodernist view that bases vocational interest and aspirations on constantly changing life roles. Previous research that examined parental influence on adolescent’s career choices, as well as research on the effects of socioeconomic status, gender, and race was included. The paper concluded with how career counselors and parents may use the strength of parental influence upon young adults to provide more effective career development techniques and create stronger partnerships with the young adult’s primary stakeholders.
Keywords: Career Choice; Parental Influence; Family Systems; Education, Vocational (0747); Sociology, Individual and Family Studies (0628)